PsGRASP, a Golgi Reassembly Stacking Protein in Phytophthora sojae, Is Required for Mycelial Growth, Stress Responses, and Plant Infection - Si, Jierui; Pei, Yong; Ji, Peiyun; Zhang, Xiong; Xu, Ruofei; Qiao, Huijun; Shen, Danyu; Peng, Hao; Dou, Daolong (Frontiers in Microbiology, 2021)
Golgi reassembly stacking proteins (GRASPs) play important roles in Golgi structure formation, ER stress response, and unconventional secretion in eukaryotic cells. However, GRASP functions in oomycetes haven’t been adequately characterized. Here, we report the identification and functional analysis of PsGRASP, a GRASP-encoding gene from the soybean-infecting oomycete Phytophthora sojae. Transcriptional profiling showed that PsGRASP expression is up-regulated at the infection stages. PsGRASP knockout mutants were created using the CRISPR/Cas9 system. These mutants exhibited impaired vegetative growth, zoospore release and virulence. PsGRASP was involved ER stress responses and altered laccase activity. Our work suggests that PsGRASP is crucial for P. sojae development and pathogenicity.